"Just Let it Pass by and it Will Fall on Some Woman": Invisible Work in the Labor Market. Issue 6 (December 2022) - Kaplan, Amit
Invisible work is neither defined nor recognized as labor and is not compensated as such. Studies show that manifestations of invisible work at home flow into the marketplace. What is lacking is systematic conceptualization and measurement of invisible work in the labor market built upon women's and men's knowledge and experiences. In this study, I address this lacuna using mixed-method sequential analysis. Twelve group interviews of employed women and men of varied socioeconomic locations in Israel yielded diverse expressions of invisible practices in the workplace and their gendered meanings. Based on that knowledge, a typology of invisible work types was deduced, and an instrument was developed and distributed through a survey to a representative sample of the Israeli labor force ( n = 964). Regression analyses revealed that women and other disadvantaged groups do more invisible work at work than men and more advantaged groups do, regardless of occupation and managerial position. Beyond that, there are varied relations between labor market position and performing invisible work, across different types of practices. The study develops a typology of invisible work as a heuristic device contributing to office housework theory. I argue that invisible work should be conceived as an integral part of the labor market that needs to be considered when studying gender inequality.